Laminated glass and preparation method thereof

By introducing a micro-nano grid layer of conductive magnetic composite material into the laminated glass, the radar detection, lightning strike, electrostatic and electromagnetic interference problems faced by existing laminated glass in special service environments are solved, and the functions of low detection, low interference and electrostatic leakage are integrated without damaging the light transmittance.

CN119526850APending Publication Date: 2025-02-28BEIJING HANGBO NEW MATERIAL TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411739506.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During service, existing laminated glass faces problems such as radar detection, lightning strike, electrostatic and electromagnetic interference, and existing methods to improve electromagnetic shielding efficiency are inevitably damaged by light transmission, and there is a lack of laminated glass with integrated functions such as low detection, low interference and electrostatic leakage.

Method used

A laminated glass structure including a first layer of glass, a second layer of glass and a micro-nano grid layer is adopted, wherein the micro-nano grid layer is made of a conductive magnetic composite material, arranged as a irregular pattern without diffraction, and is drawn out from the end of the second layer of glass to connect the frame to realize conductive connection.

Benefits of technology

Through the conductive and magnetic composite characteristics and irregular pattern design of the micro-nano grid layer, moiré stripes are eliminated, and the low electromagnetic anti-interference function of laminated glass is improved, thereby achieving low detection, low interference and electrostatic leakage effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119526850A_ABST
    Figure CN119526850A_ABST
Patent Text Reader

Abstract

The invention relates to laminated glass and a preparation method thereof, and the laminated glass comprises a first layer of glass, a second layer of glass, and a conductive and magnetic composite micro-nano mesh layer arranged on the surface of the second layer of glass and located between the first layer of glass and the second layer of glass, the micro-nano mesh layer is arranged to be non-diffracting irregular patterns, the micro-nano mesh layer is led out from the end of the second layer of glass, and the led-out part is used for being connected with a frame body. According to the laminated glass provided by the invention, the micro-nano mesh layer located between the first layer of glass and the second layer of glass is arranged on the surface of the second layer of glass, and the micro-nano mesh layer is connected with the laminated glass and the frame body. The composite characteristics of electric conduction and magnetic conduction of the micro-nano mesh layer can realize the function of low electromagnetic interference resistance, so that the laminated glass has the characteristics of low detectability and low interference in the use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of traffic equipment glass or architectural glass, and in particular to a laminated glass and a method for preparing the laminated glass. Background Art

[0002] Window materials for aircraft, ships, and special vehicles face problems such as radar detection, lightning strikes, static electricity, and electromagnetic interference in the cockpit during service. Windows of key equipment rooms, equipment compartments, ground barracks and other building facilities also face the dilemma of being detected and electromagnetic interference. There is a lack of laminated glass that integrates low detection, low interference, and static electricity discharge functions to meet the requirements of the above-mentioned special service environments.

[0003] In response to the above application requirements, the outer surface of the glass requires a transparent metallized material, but the material system, structure, and preparation method for the metallization of the outer surface of laminated glass are lacking, and the existing methods for improving electromagnetic shielding effectiveness inevitably damage the transmittance.

[0004] Based on the above background, it is urgent to develop a low-detection, low-interference laminated glass. Summary of the invention

[0005] In order to solve the above-mentioned problem of low detection and low interference function, the present invention provides a laminated glass, comprising a first layer of glass, a second layer of glass and a micro-nano grid layer, wherein:

[0006] The micro-nano grid layer is arranged on the surface of the second layer of glass and between the first layer of glass and the second layer of glass; the micro-nano grid layer comprises a conductive and magnetic composite material and is arranged in an irregular pattern without diffraction;

[0007] The micro-nano grid layer is led out from the end of the second layer of glass, wherein the led-out portion is used to be connected to the frame.

[0008] In some embodiments:

[0009] The micro-nano grid layer includes a plurality of connected curved grooves, and at least two of the grooves have different shapes and / or sizes.

[0010] In some embodiments:

[0011] The groove is in an arc shape, and outer walls of two adjacent sections of the groove are tangent to each other.

[0012] In some embodiments:

[0013] The groove includes a first annular groove and a second annular groove located in the first annular groove.

[0014] In some embodiments:

[0015] The groove further includes a connecting groove, and two adjacent first annular grooves are connected by the connecting groove.

[0016] In some embodiments:

[0017] The groove further includes a third annular groove, a third annular groove is provided between adjacent connecting grooves, and the connecting groove is located between the third annular groove and the first annular groove.

[0018] In some embodiments:

[0019] The groove includes a first annular groove, a second annular groove and a fourth annular groove; the second annular groove is located in the first annular groove and at least two of them are provided; at least one of the fourth annular grooves is circumscribed with one of the two adjacent first annular grooves, intersects with the other first annular groove and is circumscribed with at least one of the second annular grooves located inside it

[0020] In some embodiments:

[0021] A silver nanowire coating is disposed on a side of the first layer of glass away from the second layer of glass.

[0022] In some embodiments:

[0023] In the silver nanowire coating, the molar ratio of the doping amount of the silver nanowires is 1% to 10%.

[0024] The present invention provides a laminated glass, wherein a micro-nano grid layer connecting the laminated glass and the frame is arranged on the surface of the second layer of glass and located between the first layer of glass and the second layer of glass. The composite characteristics of the conductive and magnetic properties of the micro-nano grid layer and the irregular pattern thereon improve the low electromagnetic anti-interference function of the laminated glass while eliminating the moiré fringes, thereby making the laminated glass have the characteristics of low detectability and low interference during use.

[0025] Based on the laminated glass provided above, the present application also provides a method for preparing the laminated glass, which is used to prepare any of the laminated glasses described above, comprising:

[0026] S010: coating a conductive and magnetic composite slurry on one surface of the second layer of glass, and arranging an irregular pattern thereon to form a micro-nano grid layer, wherein the molar ratio of the doping amount of the magnetic material in the conductive and magnetic composite slurry is 5% to 20%;

[0027] S020: Leading the micro-nano grid layer out from the end of the second layer of glass to form a lead-out portion for connecting to a frame;

[0028] S030: stacking a first layer of glass on a side of the second glass having the micro-nano grid layer to form a laminated glass;

[0029] S040: performing a lamination process on the first layer of glass and the second layer of glass to obtain the laminated glass.

[0030] The present application obtains the above-mentioned laminated glass through the above-mentioned preparation method, obtains a micro-nano grid layer with a conductive and magnetic composite slurry, and can electrically connect the laminated glass and the frame through the micro-nano grid layer, thereby achieving the low detection and low interference effects of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of a laminated glass according to an embodiment is shown;

[0032] Figure 2 A schematic structural diagram of a micro-nano grid layer according to an embodiment is shown;

[0033] Figure 3 A schematic structural diagram of a micro-nano grid layer in another embodiment is shown;

[0034] Figure 4 shows a cross-sectional view of a conductive block in one embodiment;

[0035] Figure 5 Another cross-sectional structural diagram of a conductive block in an embodiment is shown;

[0036] Figure 6 Another cross-sectional structural diagram of a conductive block in an embodiment is shown;

[0037] Figure 7 Another cross-sectional structural diagram of a conductive block in an embodiment is shown.

[0038] Reference numerals:

[0039] 10 is the first layer of glass, 101 is the composite layer, 102 is the electric heating layer, 103 is the conductive block, 104 is the stepped metal element, and 105 is the conductive cloth;

[0040] 20 is the second layer of glass, 201 is the micro-nano grid layer, 2011 is the first annular groove, 2012 is the second annular groove, 2013 is the third annular groove, 2014 is the connecting groove, and 2015 is the fourth annular groove;

[0041] 30 is the third layer of glass; 40 is the metal outer pressure plate; 50 is the edge sealing structure; 60 is the frame; and 70 is the bolt. DETAILED DESCRIPTION

[0042] The present disclosure will now be discussed with reference to several exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and thus implement the present disclosure, rather than implying any limitation on the scope of the present disclosure.

[0043] As used herein, the term "including" and its variants are to be interpreted as open-ended terms meaning "including but not limited to". The term "based on" is to be interpreted as "based at least in part on". The terms "one embodiment" and "an embodiment" are to be interpreted as "at least one embodiment". The term "another embodiment" is to be interpreted as "at least one other embodiment". The orientation or position relationship indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like is based on the orientation or position relationship shown in the accompanying drawings. These terms are mainly for better describing the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation. In addition, in addition to being used to indicate an orientation or position relationship, some of the above terms may also be used to indicate other meanings, such as the term "upper" may also be used to indicate a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to the specific circumstances. In addition, the terms "install", "set", "provided with", "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be directly connected, or indirectly connected through an intermediate medium, or it can be an internal connection between two devices, elements or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0044] refer to Figure 1 , a laminated glass provided in an embodiment of the present application, comprising: a first layer of glass 10 and a second layer of glass 20, a conductive and magnetic composite micro-nano grid layer 201 arranged on the surface of the second layer of glass 20 and located between the first layer of glass 10 and the second layer of glass 20, so as to achieve low electromagnetic and low interference functions.

[0045] The micro-nano grid layer 201 is set to an irregular pattern without diffraction to eliminate moiré fringes and achieve a comfortable visual experience. In addition, the micro-nano grid layer 201 is led out from the end of the second layer of glass 20 to form a lead-out portion for connecting the frame 60, so as to achieve electrical conduction between the laminated glass and the body, thereby better achieving the effects of low interference, low detection and static discharge.

[0046] The above-mentioned micro-nano grid layer 201 is directly embossed on the surface of the laminated glass intermediate layer film, with a resistance value of ≤1Ω, preferably 0.1-0.5Ω, and has electromagnetic shielding performance for low-frequency bands (≤30Mhz). The micro-nano grid layer 201 is preferably a conductive and magnetic composite slurry doped with magnetic materials to achieve excellent electromagnetic shielding performance for both electric and magnetic fields, so that the laminated glass can achieve the best low-interference effect on personnel or equipment that need protection. Specifically, the molar ratio of the doping amount of magnetic material in the conductive and magnetic composite slurry is 5% to 20%. Among them, the conductive filler can be selected from silver powder, gold powder, copper powder, silver-coated copper powder, platinum powder, etc., and the magnetic filler can be selected from nickel powder, iron powder, iron-silicon-aluminum powder, iron-nickel powder, cobalt powder, beryllium-molybdenum alloy powder, etc. In the optimal embodiment of the present application, the conductive filler is preferably silver powder with good ductility and high cost performance, and the magnetic filler is preferably beryllium-molybdenum alloy powder with high magnetic permeability to achieve the best conductive and magnetic effect.

[0047] The micro-nano grid layer 201 needs to be electrically conductive with the machine body to ensure that the electromagnetic signal interference outside the laminated glass is reduced to a minimum and achieve the best electromagnetic shielding performance. Therefore, the micro-nano grid layer 201 is led out from the end of the second layer of glass 20 to form a lead-out portion for connecting to the frame 60. The length of the lead-out portion is determined according to the interface size of the laminated glass and extends to the connection portion between the laminated glass and the frame 60 to ensure that the laminated glass and the frame 60 are electrically conductive.

[0048] In one embodiment of the present application, the micro-nano grid layer 201 includes a plurality of connected curved grooves, and at least two of the grooves have different shapes and / or sizes.

[0049] In a specific embodiment, the shape of the groove is preferably an arc, and the outer walls of two adjacent grooves are tangent to each other, thereby avoiding the occurrence of stress concentration and making the laminated glass have good mechanical properties.

[0050] Specifically, the groove includes a first annular groove 2011 and a second annular groove 2012 located in the first annular groove 2011. The multiple annular groove structures are densely arranged, so that the force on the surface of the laminated glass is more balanced, and the service life of the laminated glass is improved. Preferably, at least two second annular grooves 2012 are arranged in the first annular groove 2011 to further disperse the force on the surface of the laminated glass.

[0051] In a specific embodiment, two adjacent first annular grooves 2011 are connected via a connecting groove 2014 to further balance the surface stress of the laminated glass.

[0052] Preferably, a third annular groove 2013 is arranged between adjacent connecting grooves 2014, and the connecting groove 2014 is located between the third annular groove 2013 and the first annular groove 2011. When at least three first annular grooves 2011 are closed and connected in sequence through the connecting groove 2014 to form a new annular groove structure, the third annular groove 2013 can be preferably arranged in the new annular groove structure. This allows the surface force of the laminated glass to be evenly dispersed, thereby improving the force bearing capacity and durability of the laminated glass. At least two second annular grooves 2012 are arranged in the first annular groove 2011, and two adjacent second annular grooves 2012 are arranged in an external manner, and the sizes and structures of different second annular grooves 2012 are allowed to be not completely the same. Further, the second annular groove 2012 distributed close to the first annular groove 2011 is preferably inscribed in the first annular groove 2011. The annular groove structures are mutually embedded, and while eliminating the moiré fringes, stress is further eliminated, thereby improving the force bearing capacity of the laminated glass.

[0053] See also Figure 2 , is a preferred embodiment of the present application, wherein four second annular grooves 2012 of the same size and structure are arranged in the first annular groove 2011, two adjacent second annular grooves 2012 are circumscribed, and the four second annular grooves 2012 are all inscribed in the first annular groove 2011. It can be seen that the four adjacent first annular grooves 2011 are closed and connected in sequence through the connecting groove 2014. At this time, the connecting groove 2014 is preferably a minor arc, and the two ends of the minor arc are respectively inscribed in the two adjacent first annular grooves 2011. In this embodiment, after the four adjacent first annular grooves 2011 are closed and connected in sequence through the connecting groove 2014, a new annular groove structure is formed in the middle thereof, such as Figure 2 As shown, the third annular groove 2013 is located in the new annular groove structure. In this embodiment, four third annular grooves 2013 are provided, and adjacent third annular grooves 2013 are circumscribed and inscribed in the new annular groove structure. Specifically, the size of the new annular groove structure is smaller than the first annular groove 2011.

[0054] The above-mentioned first annular groove 2011, second annular groove 2012 and third annular groove 2013 can be optionally set as circular annular grooves or elliptical annular grooves, etc., and when the first annular groove 2011 is a circular annular groove, the second annular groove 2012 and / or the third annular groove 2013 can be set as different annular groove structures.

[0055] See also Figure 3, which is another preferred embodiment of the present application, the groove includes a first annular groove 2011, a second annular groove 2012 and a fourth annular groove 2015; the second annular groove 2012 is located in the first annular groove 2011 and is provided with at least two; at least one fourth annular groove 2015 is circumscribed with one of the two adjacent first annular grooves 2011, intersects with the other first annular groove 2011 and is circumscribed with at least one second annular groove 2012 located inside it. Preferably, the shape of the fourth annular groove 2015 is elliptical, and when the elliptical fourth annular groove 2015 connects two adjacent first annular grooves 2011, it is circumscribed with one of the first annular grooves 2011, intersects with the other first annular groove 2011 and is circumscribed with at least one second annular groove 2012 inside it. Preferably, the elliptical fourth annular groove 2015 connects the two adjacent first annular grooves 2011 in the direction of the minor axis of the ellipse, and the two adjacent first annular grooves 2011 are circumscribed in the direction of the major axis. At this time, at least two second annular grooves 2012 can also be provided inside the first annular groove 2011. Here, five second annular grooves 2012 are provided as an example. Figure 3 As shown, when the five second annular grooves 2012 are arranged, one of them is located at the center of the first annular groove 2011, and the other four are distributed circumferentially around the second annular groove 2012 at the center and are simultaneously inscribed with the first annular groove 2011 and circumscribed with the second annular groove 2012 at the center. At this time, the fourth annular groove 2015 is circumscribed with the two second annular grooves 2012 away from the center. Figure 3 Preferably, the maximum dimension between two points on the first annular groove 2011 is greater than the dimension of the major axis of the ellipse.

[0056] The first annular groove 2011, the second annular groove 2012, the third annular groove 2013, the connecting groove 2014 or the fourth annular groove 2015 may also be distributed in other ways. For example, according to the size of the first annular groove 2011, a plurality of second annular grooves 2012 may be arranged therein and distributed in an annular periphery or in a straight line within the first annular groove 2011. Of course, the distribution method is not limited to the above structure.

[0057] In particular, the mesh pattern on the micro-nano mesh layer 201 is preferably a pattern of alternating combinations of embedded closed circular rings, open or closed ellipses, so as to enhance the deformation capacity of the mesh, meet the integrity of the mesh structure under the action of wind pressure and aerodynamic load, and reduce the risk of its breakage. The embedded closed circular ring is preferably embedded with four or five circular rings. In addition, a mesh pattern with other patterns or distribution methods can also be used.

[0058] When the above-mentioned micro-nano grid layer 201 is a micro-nano grid layer 201, it is manufactured by nanoimprinting technology. In addition to conventional polyethylene terephthalate (PET), the attached substrate is preferably an intermediate layer material commonly used in laminated glass, such as polyurethane film, polyvinyl butyral film, ethylene-vinyl acetate copolymer (EVA), ion-type intermediate film (SGP), etc., so as to achieve the compatibility of the micro-nano grid layer 201 with flat and curved laminated glass.

[0059] In a preferred embodiment of the present application, a silver nanowire coating is provided on a side of the first layer of glass 10 away from the second layer of glass 20 to improve the static electricity dissipation effect of the laminated glass.

[0060] The above-mentioned silver nanowire coating is directly exposed to the outdoor environment, and the resistance reaches 1MΩ~100MΩ to achieve the static discharge function. The silver nanowire coating includes silver nanowires, siloxane coatings or polyurethane coatings doped with conductive metals or metal oxide particles, poly (3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, etc. The influence of the metal doping amount on the coating resistance and transmittance is mutually restricted. Under the condition of constant resistance, the optical properties of the coating are improved as the diameter of the doped material decreases and the length increases. In this embodiment, the doped conductive material is a silver nanowire with an aspect ratio of ≥500, preferably an aspect ratio of ≥1500, and the molar ratio of the doping amount is 1%~10%, preferably 1%~7%. The small diameter of the silver nanowires at the micro-nano scale improves the transmittance, and the high length realizes good internal self-electrical lap.

[0061] In one embodiment, a composite layer 101 including a three-layer structure is provided on one side of the first layer of glass 10 away from the second layer of glass 20, and from the side close to the first layer of glass 10 to the side away from the first layer of glass 10, there are a low-detection film, a dielectric film, and a silver nanowire coating. The provision of the above-mentioned low-detection film realizes the low-detection function, the dielectric film realizes the protection of the low-detection film, and the outermost silver nanowire coating realizes the static discharge effect, and further protects the low-detection film. The low-detection film is a low-resistance transparent conductive film, and gold film (Au), silver film (Ag), indium tin oxide film (ITO), aluminum-doped zinc oxide (AZO), zinc oxide (ZnO), nanoparticle-doped metal film, etc. can be selected, and a single-layer or multi-layer conductive film is composited, and the film resistance is preferably ≤30Ω to realize the low-detection function. In order to protect the low-detection film, the dielectric film can be selected as silicon dioxide (SiO 2 ) film, silicon nitride (SiNx) film, aluminum oxide (Al 2 O 3 ) film, titanium oxide (TiO 2 ) film, transparent diamond-like carbon (DLC) film, magnesium fluoride (MgF 2 ) and other single-layer or multi-layer combination films, use optical software to design the film material and thickness to obtain the best optical performance.

[0062] In the embodiment of the present application, according to the use requirements, an electric heating layer 102 can be provided on the side of the first layer of glass 10 close to the second layer of glass 20 to realize the function of electric heating.

[0063] In one embodiment of the present application, a third layer of glass 30 is further included and disposed between the first layer of glass 10 and the second layer of glass 20 , and the micro-nano grid layer 201 is disposed on a side of the third layer of glass 20 away from the first layer of glass 10 .

[0064] See also Figure 1 , which is a laminated glass with a three-layer glass structure. At this time, the micro-nano grid layer 201 is arranged on a side of the third layer of glass 20 away from the first layer of glass 10 and is directly embossed on the film surface on the third layer of glass 20.

[0065] In a specific embodiment, electromagnetic simulation or actual measurement methods can be used to adjust the position of the micro-nano grid layer 201 in the laminated glass so that the electromagnetic wave achieves optimal loss between the first layer of glass 10 and the micro-nano grid layer 201. The position of the micro-nano grid layer 201 can be between the first layer of glass 10 and the second layer of glass 20, or between the second layer of glass 20 and the third layer of glass 30.

[0066] The laminated glass in the present application is preferably a laminated glass connected to the body with a bolted structure, such as Figure 1 As shown, the metal outer pressure plate 40 and the frame 60 are fixedly connected by bolts 70 , thereby fixing the laminated glass between the metal outer pressure plate 40 and the frame 60 .

[0067] In addition, as a preferred embodiment, refer to Figure 1, is a laminated glass provided by an embodiment of the present application, comprising: a first layer of glass 10, a second layer of glass 20, a conductive block 103, a stepped metal element 104, a conductive cloth 105 and an edge sealing structure 50. The first layer of glass 10 and the second layer of glass 20 are stacked; a composite layer 101 is provided on the surface of the first layer of glass 10 away from the second layer of glass 20; the edge sealing structure 50 is wrapped around the edge of the first layer of glass 10, and the stepped metal element 104 is embedded in the edge sealing structure 50 to limit the stepped metal element and prevent it from being displaced during use and affecting the electrical conduction between the laminated glass. The two ends of the stepped metal element 104 are respectively arranged close to the first layer of glass 10 and the second layer of glass 20, wherein the first end of the stepped metal element 104 is connected to the composite layer 101 through the conductive block 103. By providing the conductive block 103, the electrical connection between the stepped metal element 104 and the composite layer 101 can be better and more stable, thereby improving the static discharge effect. The laminated glass also includes a conductive cloth 105, one end of which is connected to the stepped metal element 104 inside the edge sealing structure 50, and the other end of the conductive cloth 105 is located outside the edge sealing structure 50 for connecting to the body, thereby achieving the effect of dissipating static electricity.

[0068] In one embodiment of the present application, the conductive block 103 is conductive rubber, and a surface of the conductive block 103 that is in contact with the stepped metal element 104 includes a curved surface. In this case, during use, the elastic deformation generated by the force applied to the contact surface of the conductive block 103 and the stepped metal element 104 will be greater, which can ensure that the conductive block 103 and the stepped metal element 104 are more fully contacted.

[0069] Specifically, the side of the conductive block 103 that is in contact with the stepped metal element 104 is wavy or concave, such as Figures 4 to 5 This arrangement enables the conductive block 103 to have multiple electrical contact portions when in contact with the stepped metal element 104, and the contact area is more secure after elastic deformation, thereby improving the reliability of the electrical connection.

[0070] More specifically, Figure 4 As shown, when the above-mentioned bonding surface is wavy, it is preferred that the wavy shape has two peaks to further increase the area of ​​the electrical contact portion.

[0071] The conductive block 103 is a conductive rubber, and the conductive block 103 is a hollow structure. After being subjected to force, the hollow conductive block 103 is more likely to produce elastic deformation and the elastic deformation produced will be greater, which can ensure that the conductive block 103 and the stepped metal element 104 are attached together, and the reliability of contact is improved, thereby improving the static discharge effect. In addition, the weight of the conductive block 103 is reduced, and its deformation coordination ability when in contact with the first layer of glass 10 and the stepped metal element 104 is greatly improved, especially the curved overlap surface.

[0072] As a preferred embodiment, the distance between the upper surface of the hollow structure close to the stepped metal element 40 when installed and the side of the conductive block 30 that is attached to the stepped metal element 40 when installed is H. 1 , which is less than the distance H between the lower surface of the hollow structure away from the stepped metal element 40 when installed and the side of the conductive block 30 that is attached to the first layer of glass 10 when installed. 2 , and H 1 <H 2 ,like Figure 4 As shown, when the conductive block 103 and the stepped metal element 104 are in contact, the contacting surfaces of the two can be more fully deformed under the action of pressure, thereby improving the stability of the electrical contact between the two and the high efficiency of static electricity discharge.

[0073] In another embodiment of the present application, the hollow structure includes a two-layer structure (upward and downward) distributed along the stepped metal element 104 toward the first layer of glass 10, and / or a two-layer structure (leftward and rightward) distributed along one end of the first layer of glass 10 close to the stepped metal element 104 toward the other end away from the stepped metal element 104. For details, see Figure 6 to Figure 7 .in, Figure 6 The conductive block 103 has two layers of hollow structures in both the up-down direction and the left-right direction. Figure 7 The conductive block 103 is a two-layer hollow structure in the left and right directions. The double-layer structure can further increase the elastic deformation, thereby making the fitting surface between the conductive block 103 and the stepped metal element 104 more stable and discharging static electricity more efficient.

[0074] The hollow structure may include a hollow sphere or a hollow hexahedron, or may include multiple hollow spheres or multiple hollow hexahedrons, or hollow structures having different shapes at the same time. In addition, the hollow structure of the conductive block 103 may also be set to the same structure as the outer shape structure of the conductive block 103, such as Figures 4 to 5 As shown, the cross-section of the conductive block 103 is a combination of a wavy and U-shaped structure. At this time, the hollow structure is also a wavy and U-shaped structure, but the cross-sectional direction of the hollow structure can be different from the cross-section of the conductive block 103, that is, the wavy and U-shaped structures of the hollow structure can be inverted or the like.

[0075] In one embodiment, a groove structure or a protrusion structure is provided on the contact surface where the stepped metal element 104 and the conductive block 103 are attached. That is, a groove structure or a protrusion structure is provided on one side of the stepped metal element 104 close to the conductive block 103 to improve the surface roughness of the stepped metal element 104, thereby enhancing the bonding strength between the stepped metal element 104 and the edge sealing structure 50 and the conductive adhesive contact interface.

[0076] The contact surface between the stepped metal element 104 and the conductive block 103 is provided with a plurality of mutually parallel groove structures and / or a plurality of mutually parallel protrusion structures. While improving the surface roughness of the stepped metal element 104, it is also easy to process. Of course, it is also feasible to set a plurality of mutually parallel, crisscross groove structures and / or protrusion structures. The present application does not specifically limit the grooves or protrusions of the other curved structures.

[0077] A protrusion structure is provided on the contact surface between the stepped metal element 104 and the conductive block 103, and the height of the protrusion structure is 1 μm to 0.1 mm to ensure the rigidity of the stepped metal element 104 and minimize the impact on its weight while improving the surface roughness of the stepped metal element 104.

[0078] In the case where the side of the conductive block 103 in contact with the stepped metal element 104 is set to a concave-convex structure, the contact portion of the stepped metal element 104 and the conductive block 103 is set to a structure that is compatible with the first surface structure of the conductive block 103. That is, if the side of the conductive block 103 in contact with the stepped metal element 104 is wavy, then the contact surface of the stepped metal element 104 and the conductive block 103 is set to a new wavy shape that is cross-coordinated with the crests and troughs that are compatible with the wavy shape of the conductive block 103, so as to further increase the contact area between the conductive block 103 and the stepped metal element 104 and improve the static discharge effect.

[0079] The conductive block 103 of the present application can be selected from flexible conductive rubber with a resistance value of ≤1Ω, the rubber substrate can be selected from silicone rubber, nitrile rubber, natural rubber, and the conductive filler filled in the rubber can be selected from silver powder, silver compound, aluminum silver-plated powder, copper silver-plated powder, carbon black, nickel powder, etc., preferably silicone rubber-based conductive rubber with good weather resistance. The stepped metal element 104 can be selected from a corrosion-resistant metal or alloy with a thickness of 0.5mm to 3mm, preferably 0.5mm to 2mm. The conductive cloth 105 can be selected from a conductive cloth with a resistance value of ≤1Ω or a flexible metal mesh-based composite fabric, such as nickel-plated conductive cloth, aluminum foil fiber composite cloth, and flexible metal mesh-based composite fabric. The length of the conductive cloth 105 is determined according to the size of the laminated glass interface to ensure sufficient electrical conduction with the body, and the length is preferably flush with the edge of the glass.

[0080] In addition, when the stepped metal element 104 and the conductive cloth 105 are arranged, there is a gap between them and the bolt holes at the edge of the laminated glass. Specifically, the gap is ≥1 mm.

[0081] The height design value of the conductive block 103 is 10% to 30% higher than the actual value of the distance between the conductive block 103 and the stepped metal element 104, so as to reserve sufficient contact deformation; the width of the conductive block 103 is 20% to 50% of the overlap size of the first layer of glass 10 and the stepped metal element 104, which can buffer the processing size error between the first layer of glass 10 and the stepped metal element 104, so as to ensure that during the service of the curved laminated glass, the first layer of glass 10-conductive block 103-stepped metal element 104 can have sufficient electrical contact, thereby improving the reliability of the static discharge function.

[0082] The conductive block 103 can be bonded and fixed in advance to a preset position on the edge of the surface of the composite layer of the first glass 10 by conductive adhesive, that is, fixed to a preset position on the edge of the surface of the composite layer 101 .

[0083] The laminated glass provided in the embodiment of the present application has a micro-nano grid layer 201 disposed on the surface of the second layer of glass 20 and located between the first layer of glass 10 and the second layer of glass 20, which connects the laminated glass and the frame 60. The composite properties of the conductive and magnetic properties of the micro-nano grid layer 201 achieve the function of low electromagnetic interference resistance, so that the laminated glass has the characteristics of low detectability and low interference during use.

[0084] The present application sets a composite layer 101 including a low-detection film, a dielectric film, and a silver nanowire coating on the outer surface of the first layer of glass 10 of the laminated glass to achieve low-detection and static discharge functions; a conductive and magnetic micro-nano grid layer 201 is set on the surface of the second layer of glass 20 to achieve electromagnetic shielding function. The composite layer 101 and the micro-nano grid layer 201 are both electrically conductive with the body to form a parallel effect, thereby enhancing the low-detection and low-interference performance of the laminated glass. An electric heating layer 102 can be added to the inner surface of the first layer of glass 10 as needed, thereby meeting multiple requirements of the transportation equipment or architectural glass field for laminated glass stealth, electromagnetic shielding, static discharge, electric heating, etc.

[0085] In addition, the present application also provides a method for preparing a silver nanowire coating. In order to reduce the encapsulation of the morphology control agent during the synthesis of the silver nanowires, increase their insulation and reduce their conductivity, a polyol method is preferably used to prepare silver nanowires with a high aspect ratio. Specifically, the polyol is preferably propylene glycol or ethylene glycol with good volatility. The preparation method is as follows:

[0086] S100: (0.2±0.1) mol AgNO 3 As precursor, ethylene glycol as solvent, add (0.2±0.1) mol Fe(NO3)3 , (2.2±1)mol NaCl, etc.;

[0087] In the embodiment of the present application, in order to improve the aspect ratio of the silver nanowires, the Ag + To generate silver nanoparticles and multiple twins, add a weak oxidant such as Fe at a molar ratio of 0.8 to 0.3 3+ , inhibitors such as Cl at a molar ratio of 0.02 to 0.005 - .

[0088] S200: reacting at a constant temperature of 80°C to 120°C for (3±1) h to obtain a silver nanowire solution with an aspect ratio of ≥500;

[0089] The aspect ratio of the silver nanowire solution is preferably ≥1500. In a preferred embodiment of the present application, the reaction is carried out at a constant temperature of 80°C to 120°C for (3±1) hours to obtain a silver nanowire solution with an average length of 90.1 μm to 70 μm and an average diameter of 48.2 nm to 20 nm. The small diameter of the silver nanowire improves the transmittance, and the long length achieves good internal self-electrical bonding.

[0090] S300: filtration to obtain pure silver nanowires;

[0091] S400: adding 1% to 10% of silver nanowires to the polysiloxane solution, blending, and obtaining a polysiloxane composite layer, namely, a silver nanowire coating.

[0092] In a preferred embodiment, 1% to 7% of silver nanowires are added to a polysiloxane solution and blended to obtain a silver nanowire coating.

[0093] The prepared silver nanowire coating is sprayed on the outer surface of the first layer of glass 10 away from the second layer of glass 20 by a spraying process, and cured for (2±0.5) hours in an environment of 80°C to 150°C, so that its resistance reaches (1 to 30) MΩ and its haze is ≤2.5%.

[0094] The present application also provides a method for preparing laminated glass, which is used to prepare the above-mentioned laminated glass, and specifically includes:

[0095] S010: coating a conductive and magnetic composite slurry doped with 5% to 20% of magnetic material on one surface of the second layer of glass 20, and arranging an irregular pattern thereon to form a micro-nano grid layer 201;

[0096] S020: Leading the micro-nano grid layer 201 out from the end of the second layer of glass 20 to form a lead-out portion for connecting the frame 60;

[0097] S030: stacking the first layer of glass 10 on the surface of the second glass 20 having the micro-nano grid layer 201;

[0098] S040: Laminating the first layer of glass 10 and the second layer of glass 20 to obtain a laminated glass.

[0099] The present application obtains the above-mentioned laminated glass through the above-mentioned preparation method, obtains a micro-nano grid layer with a conductive and magnetic composite slurry, and can electrically connect the laminated glass and the frame 60 through the micro-nano grid layer 201, thereby achieving the effects of low detection, low interference and static discharge of the present application.

[0100] In a processing example of the laminated glass of the present application, an electric heating layer 102 is plated on the inner surface of the first layer of glass 10 near the second layer of glass 20, and then the first layer of glass 10 is turned over, and a low-detection film and a dielectric film are plated on the outer surface of the first layer of glass 10 in sequence. In this embodiment, the low-detection film material is selected from an indium tin oxide composite film with a resistance of (15±10)Ω, and the dielectric film is selected from silicon dioxide. Then, a silver nanowire coating is sprayed on the dielectric film, and after curing, its resistance reaches (10~50)MΩ. The surface of the second layer of glass 20 is plated with a micro-nano grid layer 201 of silver-nickel alloy slurry, with a resistance of (0.5±0.3)Ω, and the micro-nano grid layer 201 is attached to a polyurethane film. Before lamination, the micro-nano grid layer 201 is cut to a size that can be connected to the frame 60. The first layer of glass 10, the second layer of glass 20, and the connecting materials for the bolt structure edge structure support are laminated to obtain laminated glass.

[0101] The lead-out part of the micro-nano grid layer 201 is bonded and fixed at the edge of the outer surface of the laminated glass, and the step-shaped metal element 104 is connected with the conductive block 103 and the first layer of glass 10 by the edge sealing structure 50; the sealant is applied to the end face of the laminated glass by means of a mold by means of a pouring or molding method, solidified, and demolded; then the conductive cloth 105 of a preset size is bonded and fixed at an appropriate position on the step-shaped metal element 104; finally, the lead-out part of the micro-nano grid layer 201 is extended to the lower edge of the laminated glass near the frame 60 and fixed. The laminated glass obtained by the above processing, which contains low detection, low interference and static discharge combination components, has a light transmittance of ≥70%, and has a good electromagnetic shielding effect in an electric field environment.

[0102] Low-detection films and dielectric films are preferably prepared using magnetron sputtering technology to adapt to the preparation of large-sized and special-shaped samples. Small-sized samples can be prepared using chemical vapor deposition (CVD) or physical vapor deposition (PCVD).

[0103] The silver nanowire coating for dissipating static electricity can be applied to the outer surface of the first layer of glass 10 by spraying, spin coating, blade coating, dip coating or other processes, and then cured by heating to form a film.

[0104] According to the above technical solution, the laminated glass structure and preparation method including low detection, low interference and static discharge combination components proposed in the embodiment of the present application have at least the following advantages:

[0105] 1. The composite layer 101 on the outer surface of the first layer of glass 10, the electric heating layer 102 on the inner surface of the first layer of glass 10, the micro-nano grid layer 201 on the second glass layer 20 and other materials and combined structures of the present application realize the comprehensive functions of laminated glass such as low detection, low interference, static electricity discharge, and electric heating, and provide solutions for window products serving in special environments.

[0106] 2. The composite layer 101 on the outer surface of the first layer of glass 10 of the present application adopts a low-detection film-dielectric film-silver nanowire coating structure from the inside to the outside, which on the one hand realizes the low-detection and static discharge functions of the laminated glass, and on the other hand improves the reliability of the low-detection film on the outer surface of the laminated glass.

[0107] 3. The micro-nano mesh layer 201 of the present application is preferably a micro-nano mesh layer 201 made of a conductive and magnetic composite slurry with a resistance value of ≤1Ω, which can expand the electromagnetic shielding efficiency in the low-frequency band (≤30Mhz) relative to the transparent conductive film.

[0108] 4. The low-detection, low-interference material of the present application and the body electrical conductive connection material and structure can form a parallel effect, thereby improving the low-detection, low-interference performance of the laminated glass.

[0109] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present disclosure, and in actual applications, various changes may be made thereto in form and detail without departing from the scope of the present disclosure.

Claims

1. A laminated glass, characterized in that: It comprises a first layer of glass (10), a second layer of glass (20) and a micro-nano grid layer (201), wherein: The micro-nano grid layer (201) is arranged on the surface of the second layer of glass (20) and is located between the first layer of glass (10) and the second layer of glass (20); the micro-nano grid layer (201) comprises a conductive and magnetic composite material and is arranged in an irregular pattern without diffraction; The micro-nano grid layer (201) is led out from the end of the second layer of glass (20), wherein the led-out portion is used to be connected to the frame (60).

2. The laminated glass according to claim 1, characterized in that: The micro-nano grid layer (201) comprises a plurality of connected curved grooves, and at least two of the grooves have different shapes and / or sizes.

3. The laminated glass according to claim 2, characterized in that: The groove is in an arc shape, and outer walls of two adjacent sections of the groove are tangent to each other.

4. The laminated glass according to claim 3, characterized in that: The groove comprises a first annular groove (2011) and a plurality of second annular grooves (2012) located within the first annular groove (2011).

5. The laminated glass according to claim 4, characterized in that: The groove further comprises a connecting groove (2014), and two adjacent first annular grooves (2011) are connected via the connecting groove (2014).

6. The laminated glass according to claim 5, characterized in that: The groove further comprises a third annular groove (2013), a third annular groove (2013) is provided between adjacent connecting grooves (2014), and the connecting groove (2014) is located between the third annular groove (2013) and the first annular groove (2011).

7. The laminated glass according to claim 2, characterized in that: The groove comprises a first annular groove (2011), a second annular groove (2012) and a fourth annular groove (2015); the second annular groove (2012) is located inside the first annular groove (2011) and at least two of the second annular grooves (2012) are provided; at least one of the fourth annular grooves (2015) is circumscribed with one of the two adjacent first annular grooves (2011), intersects with another of the first annular grooves (2011) and is circumscribed with at least one of the second annular grooves (2012) located inside the fourth annular groove (2015).

8. The laminated glass according to any one of claims 1 to 7, characterized in that: A silver nanowire coating is provided on a side of the first layer of glass (10) away from the second layer of glass (20).

9. The laminated glass according to claim 8, characterized in that: In the silver nanowire coating, the molar ratio of the doping amount of the silver nanowires is 1% to 10%.

10. A method for preparing a laminated glass, for preparing the laminated glass according to any one of claims 1 to 9, characterized in that: include: S010: coating a conductive and magnetic composite slurry on one of the surfaces of the second layer of glass (20), and arranging an irregular pattern to form a micro-nano grid layer (201), wherein the molar ratio of the doping amount of the magnetic material in the conductive and magnetic composite slurry is 5% to 20%; S020: Leading the micro-nano grid layer (201) out from the end of the second layer of glass (20) to form a lead-out portion for connecting to a frame (60); S030: stacking a first layer of glass (10) on a surface of the second glass (20) having the micro-nano grid layer (201); S040: Laminating the first layer of glass (10) and the second layer of glass (20) to obtain the laminated glass.